Survival or Natural Death? Issues Related to the Sustainability of Writing across the Curriculum Programmes - McLaren, Ingrid A. M.; Dyche, Caroline A.; Altidor-Brooks, Alison; Devonish, Hubert (Journal of Academic Writing, 2011)
This paper examines the issue of sustainability in Writing Across the Curriculum (WAC) programmes, focusing on the role of ‘bottom up’ initiatives in their development and spread. It argues that, although this element is essential for the start up of WAC initiatives, sustainability can only be achieved through institutionalization, a process requiring ‘top down’ measures. Since both bottom up and top down approaches are essential to successful implementation, it is critical to find the right balance between both approaches. The experience of WAC implementation at the Mona Campus of the University of the West Indies, Jamaica is used as a context within which to examine these issues. This example demonstrates a mix of bottom up and top down implementation approaches, but with insufficient top down commitment to guarantee sustainability. It concludes by looking at lessons learned and areas of continued activism which have borne some fruit. It is suggested that the issue of sustainability in the case of grassroots advocates is perhaps better conceptualized as sustained efforts to establish programmes, rather than programme sustainability per se.